Transgender student experiences of online education during COVID-19 pandemic era in rural Eastern Cape area of South Africa: A descriptive phenomenological study - Azwihangwisi Helen Mavhandu-Mudzusi; Tshimangadzo Selina Mudau; Thulile Pearl Shandu; Nthomeni Dorah Ndou (Research in Social Sciences and Technology- OpenED Network, 2021)
COVID-19 affected education in many ways. As a response, various strategies were introduced to ensure students’ access to education, including online education. For most of the students, fulltime online education brought diverse challenges. This descriptive phenomenological study explored the experiences of transgender student regarding online education during the COVID-19 pandemic in Buffalo City Metro Municipality, South Africa. Data were collected by means of individual telephonic interviews with eight purposively selected transgender students using the snowballing technique. Data were thematically analysed using the interpretative phenomenological analysis framework for data analysis. The findings indicate that transgender students faced barriers in accessing online education, including (i) limited interaction, (ii) unconducive home environment because of stigmatisation, abuse and disruptions, and (iii) lack of access to the internet owing to the centralisation of internet access points, the unaffordability of data, unstable internet connections and an intermittent electricity supply. The findings further highlighted that transgender students face stigmatisation and abuse which hinder their learning. The situation is exacerbated by a lack of sources of income for transgender students, especially those who must make means for money to buy educational resources such as data for internet connection needed for online classes. Based on the findings, the researchers recommend continuous support for transgender students to ensure their continued engagement in online education, amidst the challenges they face. To this end, educational institutions should ensure that students have alternative means of accessing education so that those from diverse populations, settings and socioeconomic statuses are reached.